Avaliação do Continence App® para prevenção de incontinência urinária em usuárias do sistema suplementar de saúde: um estudo multimétodos - Lopes, Lia Gomes (2025)
Urinary incontinence (UI) is a common and impactful symptom, especially during the pregnancy-puerperal period, which is a critical phase for prevention and treatment strategies. This study aimed to evaluate the effectiveness and user experience of the mobile application Continence App® among postpartum women in the supplementary health system. A mixed-methods study with an explanatory sequential design was conducted in two private clinics, involving 137 pregnant women divided into a control group (CG: n=72) and an intervention group (IG: n=65). In the first phase, a randomized clinical trial was conducted. The intervention group used the app, while the control group received only routine institutional care. Inclusion criteria involved pregnant women from the second trimester onward, and exclusions included women under 18, with neurological diseases, a history of UI, or cognitive impairment. Discontinuation criteria included instrumental delivery, newborn admission to a neonatal ICU, small-for-gestational-age newborns, and failure to answer phone contact after five attempts. Data collection was carried out via Google Forms, using the ICIQFLUTS, ICIQ-SF, a Knowledge, Attitude, and Practice (KAP) questionnaire on UI, and sociodemographic and obstetric data. The second phase consisted of a qualitative analysis based on telephone interviews with randomly selected participants from the intervention group. Quantitative analysis was performed using SPSS, and qualitative data were analyzed using MAXQDA. The study was approved by the Research Ethics Committee of UFC (approval number 4.651.582). At baseline, the groups were similar in terms of KAP and urinary symptoms, except for a higher urgency UI impact in the control group (CG=1.58; IG=0.42; p=0.037). At follow-up, total KAP scores were similar, but the intervention group showed a higher percentage of participants with adequate knowledge (IG: 88.2%; CG: 70%; p=0.000), while the control group had a higher rate of adequate attitude (CG: 88.2%; IG: 55%; p=0.028). No significant differences were observed between groups regarding the occurrence or impact of urinary symptoms. Intragroup analysis revealed a significant decrease in knowledge in the control group (p=0.008). The qualitative analysis revealed that low adherence to the app was mainly due to lack of time, absence of urinary symptoms, and prioritization of postpartum demands such as newborn care. Nonetheless, users positively evaluated the app. The findings suggest that perceived susceptibility and health context directly influence adherence to preventive interventions. The combination of methods allowed for a more comprehensive understanding of the results. However, limitations such as short follow-up time and low adherence hindered the detection of significant effects. The study’s strengths include the innovative use of a validated technology and the integration of mixed methods. Future research should consider longer follow-up periods, more diverse samples, and enhanced engagement strategies to better explore the role of apps in promoting urinary health.